Assessing the accuracy and generalizability of the preoperative and postoperative Karakiewicz nomograms for renal cell carcinoma: results from a multicentre European and US study. (7th March 2013) - Cindolo, Luca; Chiodini, Paolo; Brookman‐May, Sabine; De Cobelli, Ottavio; May, Matthias; Squillacciotti, Stefano; De Nunzio, Cosimo; Tubaro, Andrea; Coman, Ioan; Feciche, Bodgan; Truss, Michael; Wirth, Manfred P.; et al.
Abstract : What's known on the subject? and What does the study add?: The preoperative and postoperative Karakiewicz models for RCC are considered among the best prognostic tools available for clinical counseling. Nevertheless, their predictive acuracy was externally validated only in two papers: by the same author and in an independent sample of Asian patients. However, these models have not been externally validated in truly independent multicentre series of patients. Our study demonstrated that these models 1) provide robust prognostic information; 2) were robustly built; 3) are useful also in population far from the original series. The present results are the first to show the validity and generalizability of Karakiewicz nomograms, which are based on surgical series from European centres, for large‐, mid‐ and small‐volume European and American centres. Objective: To assess the accuracy and generalizability of the pre‐ and postoperative Karakiewicz nomograms for predicting cancer‐specific survival (CSS) in patients with renal cell carcinoma (RCC). Patients and Methods: This retrospective study included 3231 patients from European and US centres, who were treated by radical or partial nephrectomy for RCC between 1992 and 2010. Prognostic scores for each patient were calculated and the primary endpoint was CSS. Discriminating ability was assessed by Harrell's c‐index for censored data. The 'validation by calibration' method proposed by Van Houwelingen was used for checking the calibration of covariate effects. Calibration was graphically explored. Results: Local and systemic symptoms were present in 23.2% and 9.1% of the patients, respectively. The median follow‐up (FU) was 49 months. At the last FU, 408 cancer‐related deaths were recorded, Kaplan–Meier estimates of CSS (with 95% confidence intervals [CIs]) at 5 and 10 years were 0.86 (0.84–0.87) and 0.77 (0.75–0.80), respectively. Both nomograms discriminated well. Stratified c‐indices for CSS were 0.784 (95% CI 0.753–0.814) for the preoperative nomogram, and 0.842 (95% CI 0.816–0.867) for the postoperative one, with a significant difference between the two values ( P < 0.001). The covariate‐based predictions on our data for both nomograms were valid. The calibration plots showed no relevant departures from ideal predictions. Conclusions: The results suggest that the postoperative Karakiewicz nomogram discriminates substantially better than the preoperative one. These nomogram‐based predictions may be used as benchmark data for pretreatment and postoperative decision‐making in patients at various stages of RCC.